Islamist Violent Extremism: A New Form of Conflict or Business as Usual?. Issue 1 (28th September 2017) - Glazzard, Andrew; Jesperson, Sasha; Maguire, Thomas; Winterbotham, Emily
Islamist violent extremist (IVE) groups are frequently involved in civil conflicts. Indeed, some groups owe their origins to conflict, and tens of thousands of Islamists have chosen to participate in conflicts taking place in foreign countries in the past 35 years. Increasingly, IVE groups appear to have the capacity to influence the conflicts they are involved in, and are influenced in turn by their experiences. As a result, for those working on conflict resolution and post-conflict reconstruction, the involvement of IVE groups raises questions of whether traditional responses remain adequate. Drawing on three country case studies – Nigeria, Kenya and Iraq/Syria, this article examines the similarities and differences between IVE groups and other conflict actors, and what this means for development, state-building and peacebuilding responses.